Understanding Suicide Terrorism - Speckhard, A. (Nervenheilkunde, 2017)
As a terror tactic, suicide terrorism is one of the most lethal as it relies on a human being to deliver and detonate the device. Suicide terrorism is not confined to a single region or religion. On the contrary, it has a global appeal, and in countries such as Syria, Iraq, Afghanistan, and Pakistan it has come to represent an almost daily reality as it has become the weapon of choice for some of the most dreaded terrorist organizations in the world, such as ISIS and al-Qaeda. Drawing on over two decades of extensive field research in five distinct world regions, specifically the Middle East, Western Europe, North America, Russia, and the Balkans, the author discusses the origins of modern day suicide terrorism, motivational factors behind suicide terrorism, its global migration, and its appeal to modern-day terrorist groups to embrace it as a tactic.
Keywords: Suicide terrorism; Middle East terrorism; modern-day terrorism; suicide terrorism motivation; martyrdom; shaheed